ARCHITECTURE ENTERPRISE MODELS WITH TOGAF ADM AT OFFICIAL MEMBER OF BRANCH INSTITUTE EDUCATION OF MA'ARIF NAHDLATUL ULAMA IN METRO CITY - Imam Mualim (Universitas Nahdlatul Ulama Lampung, 2018)
Technology and Communications of Information (TIK) this is very needed in course development of study, but in its execution do not follow order a enterprise, can seen with system development of Information just for fulfilling an requirement to job unit division which result there no is relevant of Information system which have there is and to be woke up as solution requirement of every activity division. Education Of Ma'Arif Nahdlatul Ulama (NU) institute in Metro City find difficulties in the case integration of Information system that is change of management, what divided to become 5 School that is MI, SMP, SMA, SMK, and PT in Metro city. Constitutoing existing problem making model of enterprise in expectation improve, repair to arrange Informatioan technological management more better. Research of model of enterprise architecture Institute Education Of Ma'Arif NU in Metro city expected to yield scope of enterprise organizational in the form of especial activity and supporter activity, Architecture Vision define organizational profile, difinision of mission and vision, target of organization, organizational target, organizational unit, condition of architecture in this time and computer network.